The Boundaries of Fictio (ENTHYMEMA, 2014)
This essay surveys four articles of the section dedicated to the boundaries of fiction in literature, scientific discourse, and other areas of human creativity. The section is supposed to contribute to the study of a broad range of the problems of literary theory, such as the interaction between literature and other social practices, resulting in the creation of a particular discourse of ‘reality’ and ‘objectivity’, and the highly controversial issue of the relationship between ‘material’ and ‘form’ in the literary text.